The Practice Of Prayer As An Application Of Islamic Religious Education To The Fisherman Community On Harapan Island - Rahman, Abdul; Kasim, Hasanudin (International Journal of Educational Research & Social Sciences, 2024)
The main problem in this study is "The Practice of the Fisherman Community of Harapan Island regarding Prayer Worship". Then it is described into three sub-discussions, namely. The practice of the fishermen of the island of Harapan regarding prayer. The aim is to determine the level of worship of the fishermen community on Harapan Island. Approachused are Academic-Subjects, and Social Reconstruction. After that, conduct observations, interviews and documentation to obtain information and data in the field. Furthermore, the data obtained was selected as well as reducing what is considered unnecessary, then performs presentation and verification to test the validity of the existing data. The results of this study revealed that theoretically, the people of Harapan Island were not very proficient in explaining the meanings of worshipprayer. Pratically, it is inversely proportional to the knowledge expressed through meaning during interviews with researchers. They were a religious society, always trying to fulfill all the obligations that Allah has commanded. This is proven when they go to sea, they continue to fulfill their prayer obligations and even bring prayer equipment with them. In terms of education through prayer worship, it is by giving an example first, then informing the family of the benefits (religious, health and social) when carrying out the obligations, especially the prayer worship. Furthermore, advise family members if they do not fulfill it and provide training according to their abilities. This study has limitations on the cases observed in Fisherman Community of Harapan Island. The findings of this research provide an overview of the level of prayer implementation among the Harapan Island fishing community when going to sea.